Kualitas Layanan, Price dan Brand Image sebagai Determinan Repurchase Intention Pada Konsumen Restoran Mie Gacoan Meulaboh - Rika Qalbi; Hamdi Harmen; Ivon Jalil (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effects of service quality, price, and brand image on repurchase intention among consumers of Mie Gacoan Restaurant in Meulaboh. A quantitative approach was employed by distributing questionnaires to 100 respondents. The data were analyzed using multiple linear regression with SPSS version 27. The results indicate that service quality, price, and brand image have positive and significant effects on repurchase intention, both partially and simultaneously. Service quality was identified as the most dominant variable influencing repurchase intention. The coefficient of determination (R²) of 0.600 indicates that 60% of the variation in repurchase intention is explained by service quality, price, and brand image, while the remaining 40% is influenced by other factors outside the research model. These findings suggest that improving service quality, supported by appropriate pricing and a strong brand image, can enhance consumers' intention to repurchase at Mie Gacoan Restaurant Meulaboh.